2020
DOI: 10.1136/neurintsurg-2020-016709
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution scanning electron microscopy for the analysis of three-dimensional ultrastructure of clots in acute ischemic stroke

Abstract: BackgroundCharacterization of acute ischemic stroke (AIS) clots has typically focused on two-dimensional histological analysis of the thrombus. The three-dimensional (3D) architecture and distribution of components within emboli have not been fully investigated. The aim of this study was to examine the composition and microstructure of AIS clots using histology and serial block-face scanning electron microscopy (SBFSEM).MethodsAs part of the multi-institutional STRIP registry, 10 consecutive AIS emboli were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…Given the increased utilization of mechanical thrombectomy for the treatment of acute ischemic stroke secondary to large vessel occlusion, there has been growing interest in the analysis of retrieved thrombi 1–7. A number of studies have suggested that histopathological analysis can provide some valuable insights into stroke etiology 8–11.…”
Section: Introductionmentioning
confidence: 99%
“…Given the increased utilization of mechanical thrombectomy for the treatment of acute ischemic stroke secondary to large vessel occlusion, there has been growing interest in the analysis of retrieved thrombi 1–7. A number of studies have suggested that histopathological analysis can provide some valuable insights into stroke etiology 8–11.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a recent three-dimensional scanning electron microscopy analysis of AIS emboli showed that rt-PA treatment resulted in thinning of fibrin fibers and disruption of fibrin network which may explain the reduced clot size. 23 A recent study in an animal model reported more intima and medial layer damage after stentriever devices than with aspiration. Several factors may account for this difference, such as the mechanism of clot removal.…”
Section: Discussionmentioning
confidence: 98%
“…Although H&E staining and machine learning software allowed reproducible quantification of the three major clot components (RBCs, WBCs, and FBR), 48 the more specific MSB staining was used in many studies for the selective quantification of RBCs and FBR. 28,37,39,43,44,[49][50][51][52][53][54][55][56][57][58][59][60][61] The Picro-Mallory stain was used to assess the maturity of FBR in thrombi, based on its age-dependent differential staining. 62 Immunohistochemical staining procedures allowed the best visualization and reliable separate quantification of RBCs (glycophorin A, also designated CD235a antigen), [63][64][65] WBCs (CD45 antigen), [66][67][68][69][70] PLTs (CD41, CD42b, and CD61 antigens), 38,45,49,51,53,56,57,60,63,65,66,[71][72][73] and fibrinogen/FBR.…”
Section: Thrombus Structure and Composition: Advanced Imaging And Histopathologymentioning
confidence: 99%
“…28,37,39,43,44,[49][50][51][52][53][54][55][56][57][58][59][60][61] The Picro-Mallory stain was used to assess the maturity of FBR in thrombi, based on its age-dependent differential staining. 62 Immunohistochemical staining procedures allowed the best visualization and reliable separate quantification of RBCs (glycophorin A, also designated CD235a antigen), [63][64][65] WBCs (CD45 antigen), [66][67][68][69][70] PLTs (CD41, CD42b, and CD61 antigens), 38,45,49,51,53,56,57,60,63,65,66,[71][72][73] and fibrinogen/FBR. 49,53,63,65,66,74 Depending on the discriminatory capability of the staining procedures used, the studies expressed the ratios of clot components according to four different classifications, as shown in Table 2.…”
Section: Thrombus Structure and Composition: Advanced Imaging And Histopathologymentioning
confidence: 99%